2023
DOI: 10.1186/s12903-023-03405-0
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of elongated styloid process in the population of Barcelona: a cross-sectional study & review of literature

Hassan Assiri Ahmed,
Albert Estrugo-Devesa,
Xavier Roselló Llabrés
et al.

Abstract: Background Styloid process (SP) is a cylindrical bony projection that originates from the inferior part of the petrous temporal bone just anteriorly to the stylomastoid foramen. Several nerves, muscles, and ligaments are related closely to the (SP). It is considered elongated when the measurement exceeds 30 mm. The overall prevalence of the styloid process is between 3.3% to 84.4%. The elongation of the styloid process (ESP) is associated with the manifestation of Eagle’s Syndrome (ES) which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
(77 reference statements)
1
1
0
Order By: Relevance
“…Type I according to Langlais classification was the most common form of SP for both sides (RSP=88.0%; LSP=82.0%). Comparable results can also be found in studies already cited, marking Type I as the most common form of SP/ESP (18,23,24).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Type I according to Langlais classification was the most common form of SP for both sides (RSP=88.0%; LSP=82.0%). Comparable results can also be found in studies already cited, marking Type I as the most common form of SP/ESP (18,23,24).…”
Section: Discussionsupporting
confidence: 77%
“…However, a study on a Brazilian population was able to demonstrate partial calcification with up to 62.5% as the most common calcification form of all SPs in a large cohort (n=2,500) (22). The work of Ahmed et al from Spain also showed partial calcification as the most common calcification pattern (23). Consequently, there appears to be population-specific differences here that may require additional investigations.…”
Section: Discussionmentioning
confidence: 75%
“…The styloid process is a prominent bony protrusion that originates from the inferior section of the petrous temporal bone near the base of the skull [ 12 , 13 ]. Assiri et al reported that the styloid process is present in 3.3%-84.4% of the Saudi population overall and that 4-10.3% of individuals with the elongated styloid process have eagle's syndrome [ 14 ].…”
Section: Discussionmentioning
confidence: 99%